Financial Sustainability pada Pemerintah Provinsi di Indonesia - Aprianti, Siska; Rosada, Adelia; Choiruddin (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2025)
This study is motivated by the increasing importance of financial sustainability in regional governments to ensure the continuous provision of public services in the long term. Financial sustainability is recognized as a key indicator in maintaining fiscal stability and achieving financial independence in regional development. The objective of this research is to analyze the effects of return on assets, regional dependency, financial efficiency, and the debt-to-income ratio on the financial sustainability of provincial governments in Indonesia. This study employs a quantitative approach using secondary data obtained from audited financial reports published by the Audit Board of the Republic of Indonesia (BPK RI) for the period 2019–2023. The population consists of the financial statements of 38 provincial governments, with samples selected through purposive sampling. The data were analyzed using EViews version 12, applying panel data regression with the Random Effects Model approach. The findings indicate that regional dependency and the debt-to-income ratio have a significant negative effect on financial sustainability. Meanwhile, return on assets and financial efficiency do not demonstrate a statistically significant effect. These results suggest that financial sustainability is influenced not only by how efficiently local governments manage their resources, but more importantly by their ability to reduce reliance on intergovernmental transfers and manage debt prudently. Keywords: financial sustainability, regional dependency, regional debt. Abstrak Penelitian ini dilatarbelakangi oleh pentingnya keberlanjutan keuangan pada pemerintah daerah dalam upaya memberikan pelayanan publik secara berkesinambungan di masa depan. Keberlanjutan keuangan menjadi indikator utama bagi daerah dalam menjaga stabilitas fiskal dan kemandirian pembiayaan dalam pembangunan. Penelitian ini bertujuan untuk menganalisis pengaruh return on asset, ketergantungan daerah, efisiensi keuangan, serta debt to income terhadap financial sustainability pada pemerintah provinsi di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan data sekunder berupa Laporan Hasil Pemeriksaan yang telah diaudit oleh Badan Pemeriksa Keuangan Republik Indonesia dari tahun 2019 hingga 2023. Populasi pada penelitian ini adalah Laporan Keuangan Pemerintah 38 Provinsi di Indonesia dan sampel yang digunakan dipilih menggunakan teknik Purposive Sampling. Perangkat analisis yang digunakan dalam studi ini adalah EViews versi 12. Metode analisis yang diterapkan berupa regresi data panel dengan pendekatan random effect model. Hasil penelitian menggambarkan bahwa ketergantungan daerah dan debt to income berpengaruh negatif dan signifikan terhadap financial sustainability. Sebaliknya, return on assets dan efisiensi keuangan tidak menunjukkan pengaruh yang signifikan. Hal ini mengindikasikan bahwa keberlanjutan fiskal tidak hanya dipengaruhi oleh seberapa efisien daerah mengelola sumber dayanya, tetapi lebih dipengaruhi oleh kemampuan daerah dalam mengurangi ketergantungan terhadap dana transfer dan mengelola beban utang secara bijaksana. Kata kunci: financial sustainability, ketergantungan daerah, debt to income.